(untitled) (Revista Ciência Agronômica, 2019)
In relation to the process of eutrophication of water reservoirs, it is necessary to understand the nitrogen and phosphorus supply, as well as they contribute to the eutrophication process. The aim of this research was to quantify the input and the balance of phosphorus and nitrogen, as well as to identify the effect of climate seasonality on dynamics of these nutrients in a reservoir. The campaigns took place from April/2008 to Dec/2012 at the Orós reservoir, located in the semi-arid region of Brazil. Based on dataset it was possible to calculate the inflow and outflow of total nitrogen (TN) and total phosphorus (TP). The reservoir becoming a storage place for the nutrients transported by the flow of water from the drainage network. A total of 176 Mg of nitrogen and 230 Mg of phosphorus were retained in the reservoir. The TN and TP retained in the reservoir can lead to the water being compromised by eutrophication, increasing the financial cost of water treatment and compromising water availability for consumption use (human, livestock, irrigation and industry). Because it is a predominantly agricultural basin, and the nutrients show a similar input trend in the reservoir, it is believed that the primary source of nutrients is agriculture and livestock, also wastewater from cities around reservoir. There has been an increase in nutrient input of over time. Reservoirs in semi-arid regions are unique as regards nutrient load during dry periods, since even without fluvial input, nutrient concentrations generally remain steady or increase.